Effects of enteral nutrition and parenteral nutrition on survival in patients with advanced cancer cachexia: Analysis of a multicenter prospective cohort study. Issue 3 (March 2021) - Amano, Koji; Maeda, Isseki; Ishiki, Hiroto; Miura, Tomofumi; Hatano, Yutaka; Tsukuura, Hiroaki; Taniyama, Tomohiko; Matsumoto, Yoshihisa; Matsuda, Yosuke; Kohara, Hiroyuki; Morita, Tatsuya; Mori, Masanori; et al.
Summary: Background & aims: The benefits of artificial nutrition and hydration in patients with advanced cancer remain unknown. Therefore, we conducted a prospective study to evaluate effects of enteral nutrition (EN) and parenteral nutrition and hydration (PNH) on survival in palliative care units. Methods: This study involved a secondary analysis of a multicenter cohort study. Data of primary nutritional administration routes during the first week after admission (oral intake, enteral tube feeding, parenteral nutrition, parenteral hydration, poor oral intake) were obtained. Data of averaged calorie sufficiency rate/total calorie intake [high (75% ≤ or 750 kcal/day ≤), moderate (50–75% or 500–750 kcal/day), low (25–50% or 250–500 kcal/day), very low (<25% or <250 kcal/day)] were also obtained. After investigating the implementation of artificial nutrition and hydration, participants were divided into three groups according to the nutritional administration route and calorie sufficiency rate/total calorie intake: EN, PNH, and control. We conducted time-to-event analyses using the Kaplan–Meier method, log-rank test, and univariate and multivariate Cox regression analyses. Results: Patients were divided into the EN group ( n = 730), PNH group ( n = 190), and control group ( n = 533). Differences in survival rates among the three groups were significant (Log-rank P < 0.001). Median survival times were 43.0 (95% CI 40–46), 33.0 (95% CI 29–37), and 15.0 (95% CI 14–16) days, respectively ( P < 0.001). In the multivariate-adjusted model, a significantly lower risk of mortality was observed in Cox's proportional hazard model in the EN group and PNH groups (HR 0.43 [95% CI 0.37–0.49], P < 0.001; and HR 0.52 [95% CI 0.44–0.62], P < 0.001, respectively) than in the control group. Conclusions: This study indicated the clinical benefits of EN and PNH for patients with advanced cancer. Nevertheless, managing symptoms to improve oral intake is essential before initiation of PNH, because EN was superior to PNH. Highlights: Parenteral nutrition and hydration was administered to 34% of all patients. Enteral tube feeding was rare and unevenly distributed in head and neck cancer. Oral intake/enteral nutrition was superior to parenteral nutrition and hydration. Parenteral nutrition and hydration was superior to poor oral intake. Improving oral intake is essential even in palliative care units.